Telegram, 1928 June 11, to Wilmer Stultz, Trepassey, Newfoundland - Putnam, George Palmer, 1887-1950 (Purdue University Libraries, Archives and Special Collections, 1928)
George Palmer Putnam telegram to Wilmer Stultz, weather and takeoff prospects, June 11, 1928